Effectiveness of the "living successfully with low vision" self-management program: Results from a randomized controlled trial in Singaporeans with low vision. Issue 6 (June 2019) - Tey, Ching Siong; Man, Ryan Eyn Kidd; Fenwick, Eva K.; Aw, Ai Tee; Drury, Vicki; Chiang, Peggy Pei-Chia; Lamoureux, Ecosse L.
Highlights: As the population ages, rehabilitation programs for low vision patients are needed. Our low vision self-management program did not improve patient-centered outcomes. Future studies should consider other evidence-based models of care. Abstract: Objective: To determine the effectiveness of the "Living Successfully with Low Vision" (LSLV) self-management program to improve patient-reported outcomes in Singaporeans. Methods: In this randomized controlled trial, 165 participants with low vision (LV) were recruited and assigned to usual care (LV aid training only; N = 82) or LSLV program (N = 83). The LSLV program focuses on problem solving, coping mechanism and anticipation/preparation for future needs. The primary outcome was vision-related quality of life (VRQoL; measured using the Impact of Vision Impairment [IVI] questionnaire), while secondary outcomes included health-related quality of life; mental health; and self-efficacy, assessed at baseline, 2-weeks and 6-months post-intervention. Within- and between-group comparisons were conducted using paired t-tests and repeated measures analysis of covariance, respectively. Results: A total of 128 individuals (77.6%) completed all assessments. At 2 weeks, LSLV participants alone experienced a significant within-group improvement in the mean IVI Emotional score (P = 0.05) but not at 6 months. No other within- or between-group effects were observed. Conclusion: While SM programs have shown promising results in the management of many chronic diseases, our findings suggest that the LVSM program was not an effective approach for LV rehabilitation in Singapore. Practice implication: Other evidence-based strategies to improve QoL in patients with LV may be warranted.